Kusama : the graphic novel - Macellari, Elisa, ....-; Fortes, Edward, ....- (London : Laurence King Publishing, 2020)
From rural Japan to international icon - Yayoi Kusama has spent her remarkable life immersed in her art. Follow her incredible journey in this vivid graphic biography which details her bold departure from Japan as a young artist, her embrace of the buzzing New York art scene in the 1960s, and her eventual return home and rise to twenty-first-century super-fame.
Kusama: ossessioni, amore e arte
Keywords: Kusama Yayoi